Pelatihan Peningkatan Kompetensi English for Tourism Guru Bahasa Inggris Vokasi Pariwisata di SMK Muhammadiyah 1 Kuningan, Indonesia - Solihat, Dadang (Empowerment : Jurnal Pengabdian Masyarakat, 2025)
This community service initiative was conducted to enhance the competencies of English teachers in delivering English for Specific Purposes (ESP) instruction within the tourism sector at SMK Muhammadiyah 1 Kuningan. The primary challenges identified included teachers’ limited understanding of industry-oriented English instruction and the insufficient integration of real workplace contexts into classroom learning. The program employed a series of activities comprising needs analysis, workshop-based training, microteaching practice, and evaluation interview, practice, and teachers’ comment. The findings indicate a noticeable improvement in teachers’ comprehension of English for Tourism concepts, their professional communication skills, and their ability to design contextualized instructional materials. Overall, the program contributed positively to strengthening the quality of vocational education and enhancing teachers’ readiness to meet the demands of the tourism industry.